Biological control in a changing climate: plant-mediated impact of elevated CO2 concentration on Lobesia botrana eggs and egg parasitism by Trichogramma cacoeciae - Christine Becker; Katharina Herrmann; Annette Reineke (Journal of Pest Science, 2023)
Climate change can affect biological pest control by altering trophic interactions. Elevated carbon dioxide (CO 2 ) concentrations can reduce host plant quality and, in turn, alter herbivore and natural enemy preference and performance. Using the Geisenheim VineyardFACE (free-air carbon dioxide enrichment) facility, we studied plant- and herbivore-mediated bottom-up effects of elevated CO 2 concentration on the European grapevine moth, Lobesia botrana , and the parasitoid Trichogramma cacoeciae . Grapevine inflorescences of two cultivars cultivated at ambient or elevated CO 2 (aCO 2 and eCO 2 : 400 and 480 ppm) in the VineyardFACE were incorporated into L. botrana artificial diet. Eggs laid by the respective adults were parasitized by T. cacoeciae . Egg size and emergence rate of L. botrana as well as parasitism rate, parasitoid emergence rate and egg size preference of T. cacoeciae were evaluated. We observed an indirect grapevine cultivar-dependent bottom-up effect of CO 2 on both herbivore and egg parasitoid. Compared to aCO 2 , eCO 2 resulted in larger host eggs and higher parasitism rates regarding Riesling-feeding but not regarding Cabernet Sauvignon-feeding L. botrana larvae. Parasitoid emergence rate was higher when L. botrana had fed on Riesling compared to Cabernet Sauvignon-diet. Egg size preference depended on the host’s diet: T. cacoeciae preferred larger L. botrana eggs when the larvae had fed on grapevine-containing diet but not when they fed on standard artificial diet. Our results highlight the importance of the host’s diet for the parasitoid’s preference and performance. They furthermore suggest that the future efficiency of L. botrana -biocontrol by T. cacoeciae will not decrease under elevated CO 2 concentrations.